W kwestii kolizji art. 180 § 2 kodeksu postępowania karnego i art. 6 Prawa o adwokaturze - Mądrecka, Emilia (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article analyzes legal professional privilege in the light of provisions of the Advocate’s Profession Act, the Code of Criminal Procedure and the Code of Professional Ethics and Conduct for Advocates. The author raises the question of conflict between Art. 180 § 2 of the Code of Criminal Procedure, which regulates the advocate’s testimonial privilege and its possible waiver by court’s decision, and Art. 6 of the Advocate’s Profession Act, which treats advocate’s privilege as an absolute rule. The article also comments on the views presented in the doctrine and in judicial decisions. In addition, the author provides an interpretation of the legal regulations/norms and discusses the conflict of legal rules between these regulations. For the purpose of comparison, the article also reviews the situation of advocate–witness in civil and administrative procedures. The legal analysis concludes with proposals de lege ferenda.
Keywords: tajemnica prawnicza; adwokat; kodeks postępowania karnego; zasady etyki zawodowej; dowody niedopuszczalne; kolizja norm prawnych; świadek